EFFECTIVE MANAGEMENT OF STATE BUDGET EXPENDITURES FOR THE DEVELOPMENT OF THE SOCIAL SECTOR - Qoziyev Shodiyor Qilichboy ogli (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation. The article underscores the pivotal role of social security in the fabric of state and societal life, highlighting its dependence on the country’s economic development and social policies. Uzbekistan aims to build a robust social state, focusing on improving living conditions, education, healthcare, culture, and sports. Significant strides have been made in the past seven years, notably in expanding pre-school education coverage, increasing school capacity, and fostering private sector involvement in education and healthcare. Social security needs, rooted in the emergence of society, encompass support for children, the elderly, disabled, orphans, and temporarily or permanently disadvantaged individuals. Economic development and complex social relations further necessitate social assistance for the unemployed and economically disadvantaged.